RANCANG BANGUN KONTRUKSI DAN SISTEM GERAK SUMBU PADA MESIN FUSED DEPOSITION MODELLING - Jeffrey Jeffrey; Didi Widya Utama; Gatot Soeharsono (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Fused Deposition Modelling (FDM) is a technology additive manufacture for modelling, prototyping, and production. This technology is one of the techniques used for 3D printers. Our focus is on studying, design machines fused deposition with 3D modeling and simulation with autodesk inventor and other design tools. Design is done by simulating the strength of the construction and then determine the components needed. We are making fused deposition modeling is intended as a prototype in order to understand how it works and how to innovate in the development of fused deposition modeling. The results of the design in the form of a fused depositon modeling that is able to create physical models